Model Pembelajaran Berpusat pada Kristus untuk Transformasi Bangsa: Studi Deskriptif di Sekolah Cahaya Cemerlang - Syanti D. Mulia (SIKIP: Jurnal Pendidikan Agama Kristen, 2021)
Christian education in Indonesia has not fully taken the role of educating the young generation to know God's will, changing its paradigm, and pursuing change, personal, group, and national reform. Sekolah Cahaya Cemerlang (SCC) is a Christian educational institution that was built in order to take on a role and fulfill its vocation, with the aim of raising the next generation of leaders who bring transformation to the Indonesian nation. The research focus in this qualitative descriptive study is to describe a Christ-centred learning model at SCC in terms of policy principles, objectives, curriculum, and learning methods, involving 19 teachers,155 students, and their families. Some of the new findings from the principles of the learning process at SCC are the use of the Bible Based curriculum, the principle of partnership with families and communities, training places for young missionaries, and SCC as a learning and knowledge-sharing community. The new findings are also a holistic approach with a spiritual foundation and teachers as shepherds according to the Jesus learning model and curriculum content based on God's Word. The 'Second Home School', Bloom's Spirit-led Taxonomy, the development of the Social Domain with individual learning, and group and community involvement, form the basis for the development of learning methods at SCC. Reflexive and Transformative Learning Methods for pedagogy are also developed for the purpose of social transformation, achieving a greater Indonesia.AbstrakPendidikan Kristen di Indonesia belum sepenuhnya mengambil peran untuk mendidik generasi muda mengenal kehendak Allah, berubah paradigmanya, dan mengupayakan perubahan, refor-masi pribadi, kelompok, dan bangsa. Sekolah Cahaya Cemerlang (SCC) adalah institusi pendi-dikan Kristen yang dibangun dalam rangka mengambil peran dan memenuhi panggilannya, bertujuan membangkitkan pemimpin generasi penerus bangsa yang membawa transformasi bagi bangsa Indonesia. Fokus penelitian dalam studi deskriptif kualitatif ini adalah menggam-barkan model pembelajaran berpusat pada Kristus di SCC dari segi prinsip kebijakan, tujuan, kurikulum dan metode pembelajaran, yang melibatkan 19 guru, 155 murid beserta keluarganya. Beberapa temuan baru dari prinsip proses pembelajaran di SCC adalah penggunaan kurikulum Bible Based, prinsip kemitraan dengan keluarga dan masya-rakat, tempat pelatihan misionaris muda, dan SCC sebagai learning and sharing knowledge community. Temuan baru dalam kuri-kulum dalam penelitian ini adalah pendekatan holistik dengan dasar spiritual dan guru sebagai gembala sesuai model pembelajaran Yesus serta konten kurikulum berbasiskan Firman Tuhan.  “Sekolah rumah kedua”, Spirit-led Taksonomi Bloom, pengembangan Ranah Sosial dengan pem-belajaran individual, dan kelompok dan keterlibatan masyarakat, menjadi dasar pengembangan metode pembelajaran di SCC. Metode Pembelajaran Refleksif dan Transformatif untuk pedagogi juga dikembangkan da-lam tujuan transformasi sosial, mencapai Indonesia Maju.